At the Junction of War and Peace: On Some Legal-Military Dilemmas of the End of the Polish-Soviet War (1920–1921) - Małecki, Marian (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
This work is dedicated to the legal and military aspects of the Polish-Soviet war of 1919–1921, when after defeating the Russians in the Battle of Warsaw (August 1920), the Poles pushed the border with Russia eastward. At that time, many legal issues arose that needed to be resolved almost immediately. First, this involved the demobilization of a large number of Polish soldiers and the establishment of the Border Guard in their place, as well as allowing the State Police to establish administration alongside the local governors. Second, it concerned the restoration of discipline in the army, which, after two major Polish victories over Russia (the Battle of Warsaw and the Battle of the Niemen), required the implementation of radical punitive measures (including the introduction of the death penalty). Third, there was the issue of prisoners of war and their transfer – on the basis of exchange – to the Russian side. Fourth, finally, it was about establishing Polish administration in the occupied territories. The issue of compensation for war invalids has been presented separately.